2006
DOI: 10.1111/j.1556-4029.2006.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Abusive Prescription of Psychostimulants: A Study of Two Cases

Abstract: Because psychostimulants have serious possible side effects and particular potential for abuse, their therapeutic indications are today exclusively limited to disorders such as obesity, narcolepsy, or attention deficit/hyperactivity disorder. We report two cases of abusive prescription of these drugs. The first concerns a woman who was treated for a 3 kg weight gain with fenproporex for 5 years and presented a withdrawal syndrome when this drug was no longer marketed in France. In the second case, a woman who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…*Medication names were translated from Portuguese. †Many pill components listed would not be detected using our clinical laboratory's GC/MS technology addiction, 3,16 subarachnoid hemorrhage 17 and morphea. 18 Given the lack of monitoring of fenproporex use, it is certainly possible that other life-threatening events are currently occurring but unrecognized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…*Medication names were translated from Portuguese. †Many pill components listed would not be detected using our clinical laboratory's GC/MS technology addiction, 3,16 subarachnoid hemorrhage 17 and morphea. 18 Given the lack of monitoring of fenproporex use, it is certainly possible that other life-threatening events are currently occurring but unrecognized.…”
Section: Discussionmentioning
confidence: 99%
“…Initially developed to provide appetite suppression without stimulant effects, fenproporex has since been found to have addictive potential. 3 Fenproporex is rapidly converted in vivo into amphetamine 4 and the latter can be detected in urine for up to 60 hours after ingestion. 5 The United Nations has warned that overprescribing of amphetamine-based anorectics in South America could contribute to their international distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Zur Verlängerung der Wachperioden wird missbräuchlich Epinephrin, Coffein oder Modafinil (Vigil ® ), ein Medikament zur Behandlung der Narkolepsie als Lifestyle-Droge eingenommen, welches aber in Deutschland BTM-pflichtig ist [24]. Zu den häufigen Nebenwirkungen gehören zunehmende Nervosität und Kopfschmerzen.…”
Section: Sonstige Pharmakaunclassified
“…The included studies comprised RCT (n=25) and case reports (n=6) (45)(46)(47)(48)(49)(50). Cohort and case-control studies that complied with our inclusion criteria were not identified.…”
Section: Study Characteristicsmentioning
confidence: 99%